LEARNING TRANSFORMATION OF THE “KAMPUS MENGAJAR 7” PROGRAM THROUGH IMPROVING LITERACY AND NUMERACY AT A JUNIOR HIGH SCHOOL IN LAMONGAN - Suyitno Suyitno; Lailany Miranda Usman; Halimatus Sa'diyah; Nur Eniah; Hanifah Maghfiroh Sa'adah; Indah Dwi Pratiwi (Journal of Community Research and Engagement, 2024)
Education is an important aspect in improving the quality of human resources. Students are expected to play a professional and contributory role in the world of education, including as agents of change. The Ministry of Education, Culture, Research and Technology (Kemendikbudristek) launched Kampus Mengajar program which involves students to create interactive and meaningful learning, especially in increasing student literacy and numeracy. SMP Nurul Ummah as a disadvantaged school faces various challenges such as limited teacher human resources, school facilities, internet access and information technology, as well as socio-economic conditions which have an impact on low student learning outcomes. In implementing Kampus Mengajar program there are three implementation phases, namely the pre-assignment phase, assignment phase and post-assignment phase. Overall, the collaborative action plan that was prepared in the pre-assignment phase has been implemented well even though there are several challenges faced. The results of the Kampus Mengajar program show a significant increase in students' literacy and numeracy skills. The application of various learning innovations by students has aroused students' enthusiasm for learning. Thus, Kampus Mengajar program has helped in improving educational standards at SMP Nurul Ummah. Keywords: Transformation; Learning; Kampus Mengajar; Literacy; Numeracy